Public policy, legalization of education and nation-building: perspectives from United States and Malaysia / Mohamed Ishak Abdul Hamid and Nik Azahani Nik Mohammad - Abdul Hamid, Mohamed Ishak; Nik Mohammad, Nik Azahani (2014)
Public policy involves governments making political decisions for implementing programs to achieve societal goals, inter alia, in education, economics, security, public health and public welfare for the people. Thereafter, public policy is translated into enactment and legislation. Nation-building is a process of building a national identity using the authority of the state to form a united citizenry to foster social and political stability and independence. It involves the social engineering of the populace to influence popular development of attitudes, social behaviours, values, language, institutions and public monuments. The governments of United States and Malaysia have endorsed public policies and legislations that enable the nationhood aspiration to become a reality. One of the vehicles to achieve nationhood is via the legalization of education. The evidence of the legalization of education in the United States, Malaysia and elsewhere is irrefutable. The experiences of the United States and Malaysia throughout their history in embracing such public policy, legalization of education and nationbuilding expose that such process lead to progressive nation-building and nationhood. This study involved library as well as field research, focusing on the legislations relating to education in the United States and Malaysia and where applicable other common law jurisdiction. The approach of the study covered both descriptive and inferential statistical analysis of surveys conducted on educators, educational administrators and educational institutions.